Dampak Keterbatasan Sumber Daya Manusia terhadap EfektivitasPengelolaan Keuangan pada BLUD RSUD Campurdarat - Ibravita Dwi Annisa; Sindy Nur Aisyah; Riska Amellia Putri; Elysia Septi Amanda; Aqilla Nabbihah; Irfan Fauzi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine how the limited human resources of the Regional Public Service Agency (BLUD) of Campurdarat Regional Hospital affect the efficiency of financial management. The background of this study is the lack of professional human resources (HR) in the financial sector, which can hinder the effectiveness, accuracy of reporting, and transparency of hospital financial governance. To obtain a comprehensive picture of the financial management situation at Campurdarat Regional Hospital, the methodology used was interviews, observation, and documentation studies. This research in the study findings shows that although financial management has been implemented in accordance with regulations, such as the values of transparency and accountability, the lack of human resources causes a number of problems, including high employee workloads, delays in financial reporting, and errors in recording drug receivables to third parties. This condition will hamper cooperation between units and reduce the effectiveness of internal supervision. The quality of human resources is a crucial component in realizing effective and efficient public financial governance, according to institutional and resource theories. Therefore, to ensure more effective, accountable, and sustainable financial management in the Campurdarat Regional Public Service Agency (BLUD), capacity building through continuous training, recruitment of professional staff, and optimization of the role of the Internal Supervisory Unit (SPI) is very crucial.